Hallo? Nedslag i telefonens litteraturhistorie - Andersen, Tore Rye (Passage - Tidsskrift for litteratur og kritik, 2014)
Tore Rye Andersen: “Hello?: Episodes in the Literary History of the Telephone” Through analyses of three American novels – Francis Scott Fitzgerald’s The Great Gatsby (1925), Thomas Pynchon’s The Crying of Lot 49 (1966) and Jennifer Egan’s A Visit From the Goon Squad (2010) – this article traces the major impact that the invention of the telephone has had on both society and the culture that reflects it. The medium of the telephone has thoroughly restructured the social space that is one of literature’s most important topics, and it has provided authors with new narrative strategies, new metaphors, new topics and new props, some of which are discussed in the article. The three analyses focus on different stages in the technological development of the telephone, and together they demonstrate how changes in the medium of the telephone also result in changed possibilities for literature.